Locally adapted farmer managed natural regeneration technology with microdosing and manure application - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
The Sahel (implemented using planned comparisons with performance measurement across 1789 farmers in 5 regions of Niger in conjunction with GLDC http://www.worldagroforestry.org/sites/default/files/Restoration%20of%20Degraded%20Land%20Project%20Brief%20Feb%202018.pdf